(2009+2008*2010)/(2009*2010-1)+(2010+2009*2011)/(2010*2011-1)+(2011+2010*201

来源:学生作业帮助网 编辑:六六作业网 时间:2024/03/03 11:17:00
(2009+2008*2010)/(2009*2010-1)+(2010+2009*2011)/(2010*2011-1)+(2011+2010*201(2009+2008*2010)/(2009*2

(2009+2008*2010)/(2009*2010-1)+(2010+2009*2011)/(2010*2011-1)+(2011+2010*201
(2009+2008*2010)/(2009*2010-1)+(2010+2009*2011)/(2010*2011-1)+(2011+2010*201

(2009+2008*2010)/(2009*2010-1)+(2010+2009*2011)/(2010*2011-1)+(2011+2010*201
(2009+2008*2010)/(2009*2010-1)+(2010+2009*2011)/(2010*2011-1)+(2011+2010*2012)/(2011*2012-1)
=[2009+(2009-1)(2009+1)]/(2009*2010-1)+[2010+(2010-1)(2010+1)]/(2010*2011-1)+[2011+(2011-1)(2011+1)]/(2011*2012-1)
=(2009+2009^2-1)/(2009*2010-1)+(2010+2010^2-1)/(2010*2011-1)+(2011+2011^2-1))/(2011*2012-1)
=[2009(1+2009)-1]/(2009*2010-1)+[2010(1+2010)-1]/(2010*2011-1)+[2011(1+2011)-1]/(2011*2012-1)
=(2009*2010-1)/(2009*2010-1)+(2010*2011-1)/(2010*2011-1)+(2011*2012-1)/(2011*2012-1)
=1+1+1
=3

(2009+2008*2010)/(2009*2010-1) 2008*2010=(2009-1)(2009+1)=2009^2-1
2009+2008*2010=2009+2009^2-1=2008+2009^2
2009*2010-1=2009 *(2009+1)-1=2009^2+2009-1=2008+2009^2
(2009+2008*2010)/(2009*2010-1) =1
所以原式=3